TITIK TETAP REICH DI DALAM RUANG b-METRIK - Ahmad Khairul Umam; Krisna Adilia Daniswara (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Problem of linear equation, integral equation, and differential equation can be solved with a fixed point. One of generalization of metric space is b-metric space. This article discusses a lemma, a theorem and an example in b-metric space. We discuss a theorem about uniqueness and existence of fixed point.